Therapeutic drug monitoring in adolescents with anorexia nervosa for safe treatment with adjunct olanzapine - Karwautz, Andreas; Zeiler, Michael; Schwarzenberg, Julia; Mairhofer, Dunja; Mitterer, Michaela; Truttmann, Stefanie; Philipp, Julia; Koubek, Doris; Glüder, Maria; Wagner, Gudrun; Malcher, Anouk; Schöfbeck, Gabriele; et al. (European eating disorders review, 2024)
Objective Medication is commonly used in anorexia nervosa (AN) despite largely missing high grade evidence. Olanzapine (OLZ) is the best-evidenced substance used off-label in this group, with conflicting outcome regarding BMI, clinical and safety parameters. Therefore, it is important to strictly assure quality of treatment with OLZ in AN by using ‘Therapeutic Drug Monitoring’ according to AGNP-guidelines, including serum levels and adverse drug reactions (ADRs) to support safety for adolescents with AN and attempt to generate an initial age- and disorder-specific therapeutic reference range. Method Sixty-five adolescents with AN (aged 10-18) treated with OLZ (98% female; 97.5% AN-restricting-type) were prospectively observed, ADRs reported, and correlations between dosage and serum levels measured at trough level were calculated, a preliminary therapeutic range defined. Results Mean dosage of OLZ was 8.15 (SD: 2.91) mg and 0.19 (SD: 0.07) mg/kg respectively, average concentration was 26.57 (SD: 13.46) ng/mL. Correlation between daily dosage/dosage per kg and serum level was 0.72 (**p < 0.001)/0.65 (**p < 0.001), respectively. ADRs with impairment were rare (6.3%). 75% improved clinically (CGI). BMI increased significantly by 1.5 kg/m2 (t = 10.6, p < 0.001). A preliminary therapeutic reference range is 11.9 and 39.9 ng/mL. Conclusions OLZ in the hands of specialists is a well-tolerated and safe treatment adjunct for adolescents with AN.
Zuerst veröffentlicht: 17. August 2023
Gesehen am 24.06.2024